Experimental evaluation of eccentric rotational channel-type damping system for vibration control of building structures. Issue 2 (January 2020) - Kim, Hyeong-Gook; Kim, Kil-Hee
A theoretical and experimental investigation of an eccentric rotational channel-type damping system is presented. The proposed damping system can incorporate any type of existing passive dampers and provide a wider field of view to residents compared with existing damping systems. Furthermore, the efficiency of the proposed damping system can be magnified by modifying the geometry of the channel-type secondary system. Cyclic loading and free vibration tests of a full-scale test model with steel dampers were conducted to investigate the validity of the suggested simple behavior prediction model and the vibration characteristics of the proposed damping system. The experimental results were in good agreement with the numerical analysis. The results of numerical prediction studies on a single degree of freedom system with the proposed damping system also showed the effect of the eccentric rotational channel-type damping system on seismic response reduction.